The effect of environmental stressors on anti-mullerian hormone levels in Lebanese women: a retrospective study - Sima Fatima Sharafeddin; Zeina Chehade; Samya El Sayed; Dima Salloum; Lara Nahouli; Antoine Hannoun; Ghina Ghazeeri (PLoS ONE, 2025)
Background Prolonged and repetitive exposure to stressors leads to detrimental effects on female reproductive health; this can consequently increase susceptibility to stress and elevate risk of adverse mental health outcomes. Since October 2019, Lebanon has been engulfed in a multipronged crisis, beginning with a severe economic collapse, which was further exacerbated by the COVID-19 pandemic, followed by the catastrophic Beirut Blast in August 2020. These compounding events caused considerable stress, resulting in a substantial mental health burden. We employed a retrospective approach to trace the trend in Anti-Mullerian Hormone levels (the most widely used measure of functional ovarian reserve) in a sample of reproductive-aged Lebanese women in a tertiary healthcare center in Beirut in light of the events described. Methods A retrospective chart review was performed of women aged 18–40 with AMH levels tested between January 2018 and June 2023 [excluding the time period between February 2020 – December 2020] (n = 563). Patients who had AMH levels between January 2018 – January 2020 were included in the ‘pre-stressful events’ group (n = 254) while those tested between January 2021 – June 2023 were in the ‘post-stressful events’ group (n = 283). Patient’s age, BMI, obstetrical and gynecological history, AMH level, and other relevant lab values were collected. Results were compared using the independent t-test. Results Overall, this study demonstrated a lower mean AMH level in the post-stressful events group as compared to the pre-stressful events group, but this difference was not statistically significant. Patients with PCOS had a significant decline in the mean AMH level, as did patients with primary infertility. Conclusion Women with pre-existing reproductive health disorders, such as PCOS and infertility, are more vulnerable to stress and are more likely to experience a decline in AMH level and, by extension, ovarian reserve following stressful experiences.